Flow Cytometric Findings in Clonal Cytopenia of Undetermined Significance. Issue 2 (20th September 2021) - Nirmalanantham, Priyatharsini; Sakhi, Ramen; Beck, Rose; Oduro, Kwadwo; Gadde, Ramya; Ryder, Chris; Yoest, Jennifer; Sadri, Navid; Meyerson, Howard J
Abstract: Objectives: To examine flow cytometric (FCM) findings in clonal cytopenia of undetermined significance (CCUS) in relation to variant allele fraction (VAF) and mutation risk. Methods: Nine FCM parameters, including 5 FCM metrics (Meyerson-Alayed scoring scheme [MASS] parameters) we previously used to identify myelodysplastic syndromes (MDS), were compared among 96 CCUS samples, 100 low-grade MDS samples and 100 samples from patients without somatic alterations (controls). Results: FCM findings did not differ between CCUS samples with less than 20% VAF and controls. CCUS samples with more than 20% VAF (CCUS >20% VAF) demonstrated more than 1 abnormal FCM parameter at a frequency between MDS and controls. Abnormalities in CCUS with high-risk alterations (CCUS(hi)) were similar to MDS, with no statistical difference in the percentage of cases with more than 1 FCM abnormality or a positive MASS score. The positive predictive value (PPV) for clinically significant myeloid processes; MDS, CCUS(hi), and CCUS >20% VAF compared with other CCUS samples and controls was 94.8%, with 96.5% specificity and 61% sensitivity using a modified MASS score. A subset of MDS (43%) was distinguished from CCUS(hi) and CCUS >20% VAF using 3 parameters, with a 93.5% PPV and 83.3% specificity. Conclusions: FCM abnormalities can distinguish high-risk CCUS based on VAF or alteration type from low-risk CCUS and MDS in many cases. The findings are of potential utility in the evaluation of patients with cytopenias.